MINERALOGICAL AND GEOCHEMICAL FEATURES OF HEAVY CONCENTRATES FROM CREEKS OF THE NORTHWESTERN END OF THE OKHOTSK TERRANE (KHABAROVSK KRAI) - М.А. Pavlova; D.I. Smirnov; D.А. Guskov; S.V. Petrov; M.A. Rassomakhin; A.Yu. Nefyodova (Минералогия)
The work presents the mineralogical and geochemical features of heavy concentrates from eight gold-bearing tributaries of the Anmandykan 2nd Creek in Khabarovsk krai: West otvilok, East otvilok, Somnitelny, Smezhny, Perevalny, Sobol, Vstrechny and Khvory. The mineral composition of heavy concentrates of the right creeks differs from those of the left ones by a significantly higher percentage of minerals of the garnet group, sulfides and native gold and a lower content of zircon and amphiboles. Garnets in heavy concentrates have different compositions and belong to the almandine and grossular-andradite series. Native gold grains in placers are yellow, small, mostly weak and medium-rounded, often with inclusions of quartz, feldspar, pyrite, iron oxides and hydroxides, and zircon. The native gold grains have low fineness and contain only Ag. The native gold grains are rimmed by thin, intermittent, porous aggregates of high-fineness gold. Two gold placer mineral assemblages are identified, which include native gold, chalcopyrite, sphalerite and pyrite in assemblage 1 and native gold, scheelite and minerals of the garnet group (mainly of the grossular-andradite composition) in assemblage 2. Our data allow the forecast of the presence of two primary gold sources of goldquartz-sulfide and skarn types. The comparison of results of mineralogical and geochemical studies showed their suitability and expressiveness for the interpretation of geological and metallogenic features of the studied area.